Covering of Gender Issues in Japanese Mass Media - Бaлaкaевa Л. Т.; Aбеуовa Д. М. (Journal of Oriental Studies, 2017)
This article aims to identify current trends in covering of gender issues in Japanese Mass Media. It notes the uniqueness of Japanese journalism that made a tangible impact on its structure and specificity. It is shown how the media not only reflects the change in the status of women by just stating the facts, but also actively perpetuates the stereotypes about the role of women in society through films, serials, newspapers, magazines and the Internet.